Exposure of Indian RAFM under variation of He+ flux and target emperature in the CIMPLE-PSI linear device. (15th September 2020) - Sarmah, Trinayan; Dihingia, Pubali; Rahman, Mizanur; Ghosh, J.; Chaudhuri, P.; Srivastava, Divesh N.; Satpati, B.; Kumar, Sanjiv; Kakati, M.; Temmerman, G. De
Abstract: The paper reports first investigations of the effect of low-temperature helium (He) plasma exposure on the India specific reduced activation ferritic martensitic (IN-RAFM) steel. Experiments are performed in the CIMPLE-PSI device, over the variation of ion-flux (∼3 × 10 22−23 m −2 s −1 ) and target temperature (316 K−830 K), for ion-fluence up to 1.6 × 10 26 m −2 . Strong morphology changes have been observed, in particular, fiber-form surface structures with nanometer-sized grain structures, pinholes, and hollow fibers. Surface enrichment of tungsten up to 2.3 at.% was measured by energy dispersive x-ray spectroscopy (EDX), which was supported by Rutherford backscattering spectrometry (RBS) measurements. This had happened because iron and chromium were preferentially sputtered out by the He ions. It is demonstrated that the porous, micrometer-sized surface inhomogeneities, produced under high ion-flux (≥8.0 × 10 22 m −2 s −1 ) and high target temperature (≥518 K), critically influence the shape of the RBS spectrum, which necessitates a revision of the data analysis procedure. Through optical emission spectroscopic observations, we demonstrate that the sputtering yield of the steel decreases with exposure time, primarily because of the formation of the porous surface microstructures and also due to the surface enrichment of the exposed samples with tungsten atoms. It is concluded that the formation of bubbles underneath the surface of RAFM, and their subsequent distortion and rupturing leads to the formation of fiber-form structures under the relatively high target temperature, high ion-flux irradiation conditions.